Observational Assessment of Engagement Strategies to Promote Parent Homework Planning in Community-Based Child Mental Health Treatment: A Pilot Study - Martinez, Jonathan I. (J Child Fam Stud, 2018)
Therapy homework includes tasks given to clients to complete outside of session to facilitate new knowledge/skills or to advance treatment goals. Homework completion, an important element of parent engagement in child mental health (MH) treatment, has been associated with improved child outcomes. The current pilot study assessed the design/assign phase of the therapy homework process to examine a) the extent to which therapists implemented engagement strategies with parents and b) whether therapist deployment of engagement strategies in early treatment predicted subsequent parent participation in homework planning. We included an ethnically-diverse sample of 10 therapists and 11 parent/child dyads receiving community-based MH services who participated in a pilot intervention study. Two observational coding systems were developed to code treatment session recordings for the extent to which a) therapists implemented engagement strategies with parents and b) parents contributed to therapy homework planning. Findings revealed low extensiveness of therapist implementation of engagement strategies with parents. As hypothesized, therapist use of engagement strategies (Collaboration, Empowerment, and Psychoeducation) in early treatment significantly predicted subsequent parent homework planning (sharing perspective on homework planning). However, therapist use of Alliance was unrelated to parent homework planning. These preliminary results suggest that therapist implementation of engagement strategies in early treatment may promote parent participation in homework planning, which is an important precursor to homework completion. This pilot study suggests potential future directions for both research on and training for community-based therapists in implementing successful strategies to promote parent homework planning in child MH treatment.